Evaluation of the history book for the sixth grade literary in the light of contemporary global trends (Journal of the College of Basic Education, 2024)
The current research aims to evaluate the history textbook for sixth-grade literary class in light of contemporary global trends. To achieve the research objectives, a descriptive analytical approach was employed. After reviewing the literature and previous studies on the subject, researchers compiled a list of criteria for contemporary global trends, consisting of 42 standards distributed across seven areas: decolonization of knowledge, flexibility of curricula for multimedia, comprehensive and technological education, application-based learning curriculum, inclusion of social and emotional learning, leveraging digital technology in education, environmental curriculum, and integration of research and innovation as curricular dimensions.The validity of these criteria was verified by presenting them to a panel of experts, and their reliability was ensured using a test-retest method. The analysis tool was applied during the second semester of the academic year (2023-2024). After collecting and statistically analyzing the data using frequencies and percentages (commonality coefficients), the following results were obtained:. 1The history textbook for sixth-grade literary class included 17 out of the 42 standards of contemporary global trends in curricula, while 25 standards were not included.. 2The percentage of ideas not covered by contemporary global trends standards in the sixth-grade literary class textbook was 62.7%, whereas the percentage of ideas covered by these standards was 37.2%.